PERAN PEMERINTAH DAERAH TERHADAP PEREDARAN MAKANAN TIDAK SEHAT DAN BELUM SERTIFIKAT HALAL DI WILAYAH PARIWISATA ACEH - Irwandi, Irwandi (International Journal Mathla’ul Anwar of Halal Issues, 2023)
Food is not just about halal and haram laws, but the quality (nutritional content) and effect of food on body health. Many diseases are caused by consuming foods that contain dangerous substances. So it is not surprising that the Prophet was very concerned about food issues. Good and halal food is food that is considered good by normal human instincts, or is considered good by all humans. For Muslims, there is one factor that is even more important, namely the relationship between whether food is halal or haram. Muslims are taught to eat clean and healthy food. Islam is very concerned about the source and cleanliness of food, how to cook, serve and eat food. that the regional government's efforts to deal with unhealthy food in the school environment have not been properly realized due to a lack of socialization and supervision from related parties, this is indicated by the fact that there are still many snacks in circulation that do not meet the standards stated in Minister of Health Decree No. 942/MENKES/SK/ VII/2003 concerning Guidelines for Hygiene Sanitation Requirements for Snack Foods and Law Number 36 of 2009 concerning Health and Government Regulation Number 28 of 2004 concerning Food Safety, Quality and Nutrition. In the view of Islamic law and Positive Law, the government is obliged to provide protection to all Muslim consumers from the distribution of unhealthy food and must be halal. Where the steps taken by the government are to make regulations relating to the protection of Muslim consumers against unhealthy and halal food products, there are no specific regulations that require every business to have a halal certificate.